2017
DOI: 10.3892/ol.2017.7107
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic significance of cyclin‑dependent kinase inhibitor 1A in patients with resected gastric adenocarcinoma

Abstract: Abstract. Cyclin-dependent kinase inhibitor 1A (CDKN1A) is an important cell cycleregulator, and has been identified to exhibit aberrant expression in various types of cancer tissues. However, the association between CDKN1A expression level and prognosis in patients with resected gastric adenocarcinoma (RGA) requires additional elucidation. In the present study, the CDKN1A expression profile in RGA tissues obtained from 217 patients were analyzed using immunohistochemistry. Its prognostic significance was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Therefore, CDKN1A is an indicator of tumor characteristics and may be used to predict patient prognosis. A previous study also indicated that differential expression of CDKN1A affected prognosis in the survival analysis of patients with gastric cancer (44). In this study, the GSE21510 and GSE32323 datasets were analyzed.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, CDKN1A is an indicator of tumor characteristics and may be used to predict patient prognosis. A previous study also indicated that differential expression of CDKN1A affected prognosis in the survival analysis of patients with gastric cancer (44). In this study, the GSE21510 and GSE32323 datasets were analyzed.…”
Section: Discussionmentioning
confidence: 90%
“…It involves in G2/M checkpoint that contributes to resistance to Taxol-induced apoptosis in ERBB2-overexpressed breast cancer cells (Kreis et al, 2019). Moreover, CDKN1A has demonstrated important prognostic significance and may be used as an independent prognostic factor for patients with RGA (Lin et al, 2017). In our study, we analyzed the molecular interaction of pyrogallol with p21 protein, with a binding energy value of −3.79 kcal/mol, and in vitro study shows that pyrogallol suppresses the expression of p21.…”
Section: Discussionmentioning
confidence: 99%